A study of contact properties between molybdenum and amorphous silicon tin oxide thin film transistors. Issue 12 (21st September 2018) - Ning, Honglong; Liu, Xianzhe; Xu, Hua; Lu, Kuankuan; Zhang, Hongke; Zhang, Xiaochen; Yao, Rihui; Fang, Zhiqiang; Wang, Xiaofeng; Peng, Junbiao
Abstract: Amorphous silicon tin oxide (a‐STO) semiconductor is of increasing interest for fabricating thin film transistor. The contact properties of Mo source/drain electrode to a‐STO film subjected to different thermal annealing processes was investigated. The formation of molybdenum oxide interlayer between Mo and a‐STO film annealed in air ambient was confirmed by cross‐sectional transmission electron microscopy image, and the interlayer was formed by getting oxygen from a‐STO film in air annealing process. The formation of molybdenum oxide interlayer could provide not only an adhesive layer but also an intermediate barrier layer, and it hindered Mo atoms diffuse into a‐STO film, which would form a good quality of contact interface and facilitate the electron injection from Mo electrode into a‐STO film. Abstract : We demonstrated that the molybdenum oxide interlayer was formed between Mo and amorphous silicon tin oxide film. It not only hindered the diffusion of Mo atoms, improved the quality of contact interface, but also further facilitated the electron injection.